Factores predisponentes de intolerancia social en la infancia en un adulto en fase crónica de alcoholismo - Ospina Varela, Angie Camila (Universidad Antonio Nariño, 2021)
This research aimed to identify the predisposing factors of social intolerance in the childhood of a 36-year-old adult. For this, the AUDIT test and the life history were used as instruments, the research has a single case study design which allows a semi-structured interview to be carried out with the interviewee where the main results were evidenced that among the predisposing factors during childhood There is domestic violence, low income and an alcoholic father, which led the interviewee to acquire a life model merced in alcohol and behaviors of social intolerance exercised in the family and society.